Mitochondrial DNA Copy Number in Rett Syndrome Caused by Methyl-CpG-Binding Protein-2 Variants - Liu, Siwen; Pei, Pei; Li, Lin; Wu, Hairong; Zheng, Xuefei; Wang, Songtao; Xiao, Yang; Pan, Hong; Bao, Xinhua; Qi, Yu; Ma, Yinan (The Journal of pediatrics, 2022)
To determine changes in mitochondrial DNA (mtDNA) copy number in peripheral blood in Rett syndrome caused by methyl-CpG-binding protein-2 (MECP2) variants and explore the mechanism of mitochondrial dysfunction in Rett syndrome. Female patients who were diagnosed with Rett syndrome and had an MECP2 variant (n = 142) were recruited in this study, along with the same number of age- and sex-matched healthy controls. MtDNA copy number was quantified by real-time quantitative polymerase chain reaction with TaqMan probes. The differences in mtDNA copy number between the Rett syndrome group and the control group were analyzed using the independent-samples t test. Linear regression, biserial correlation analysis, and one-way ANOVA were applied for the correlations between mtDNA copy number and age, clinical severity, variant types, functional domains, and hot-spot variants. MtDNA copy number was found to be significantly increased in the patients with Rett syndrome with MECP2 gene variants compared with the control subjects. Age, clinical severity, variant types, functional domains, and hot-spot variants were not related to mtDNA copy number in patients with Rett syndrome. MtDNA copy number is increased significantly in patients with Rett syndrome, suggesting that changes in mitochondrial function in Rett syndrome trigger a compensatory increase in mtDNA copy number and providing new possibilities for treating Rett syndrome, such as mitochondria-targeted therapies.